A Simple, Fast, and Effective LL(1) Error Repair Algorithm - Fischer, Charles N; Mauney, Jon (University of Wisconsin-Madison Department of Computer Sciences, 1989)
Validation and locally least-cost repair are two simple and effective techniques for dealing with syntax errors. We show how the two can be combined into an efficient and effective error-handler for use with LL(1) parsers. Repairs are computed using an extension of the FMQ algorithm. Tables are created as necessary, rather than precomputed, and possible repairs are kept in a priority queue. Empirical results show that the repairs chosen with this strategy are of very high quality and that speed is quite acceptable.